Implementasi Rasa Syukur Dalam Mewujudkan Kebahagiaan - Nanda Amiroh Fauziyyah; Nabila Khusna (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
Happiness is a crucial element in human life, where gratitude is believed to have a significant influence in achieving it. This study aims to explore the application of gratitude in daily life and its impact on individual happiness levels. Using a mixed methods approach, this research combines quantitative and qualitative methods to gain a deeper understanding. Quantitative data was collected through the distribution of a 15-item questionnaire to approximately 142 respondents from diverse social and economic backgrounds. Data analysis was conducted using SPSS software with linear regression tests to identify the relationship between gratitude and happiness. Meanwhile, qualitative data was obtained from various literature sources, particularly Tafsir Jalalain and Tafsir Ibnu Kathir, as well as several relevant scientific articles. The results of the study indicate that the practice of gratitude plays a vital role in enhancing happiness, both from subjective and objective perspectives. Therefore, cultivating the habit of gratitude serves as a significant strategy for improving psychological and social well-being, both at the individual and community levels.